SUSTAINABLE DEVELOPMENT OF LUMUT PORT. AN OVERVIEW - Aminuddin Md Arof; Norazlina Abdul Nasir; M.R. Zoolfakar (Marine Frontier, 2018)
As part of an effort to enhance port capacity in handling bulk and general cargo, Lumut Port has decided to construct a new terminal along the Manjung (Dinding) River, opposite its present location. Therefore, this paper aims to present an overview on the effects of reclamation of mangrove swamp along the river, the deepening of the river and construction activities on and along the river front to the surrounding marine environment as part of the expansion plan of Lumut port. This study concludes with several recommendations to mitigate the impact of the new port development to the marine environment particularly those involving reclamation of mangrove swamp, deepening of the river basin and construction work at or near the river